O18-1 Epigenetic effects of occupational exposure to carbon nanotubes. (1st September 2016) - Ghosh, Manosij; Öner, Deniz; Tabish, Ali M; Poels, Katrien; Hoet, Peter; Pronk, Anjoeka; Vermeulen, Roel; Bekaert, Bram; Godderis, Lode
Abstract : The present study was designed to assess the epigenetic alterations induced by occupational exposure to carbon nanotubes (CNT). We included 8 operators, 16 R&D workers and 43 controls. The presence of CNT in the workplace was measured during the study period. Aggregates of CNT in the size range of 200 nm–100 μm were found in the production and R&D work space, with concentrations of 4.6–42.6 μg/m 3 . We analysed DNA from blood samples for possible epigenetic alterations (global and gene specific DNA methylation). A preliminary analysis of global DNA methylation and hydroxymethylation with adjustment for age, gender and smoking status did not reveal significant difference between the CNT exposed and control groups. Further analysis of gene-specific DNA methylation patterns by pyrosequencing provided some evidence of an association between CNT exposure and DNA methylation. While no significant change in CpG methylation was observed for LINE 1, ATM, SKI and HDAC 4 genes, a significant hypermethylation was observed for DNMT1 in the R&D workers. Since DNA methylation plays an important role in several biological processes through epigenetic silencing/regulation of genes, an aberrant methylation of DNMT1 might have a significant effect in various cellular processes, which remain to be clarified.